Reassortment and adaptive mutations of an emerging avian influenza virus H7N4 subtype in China. - Bingqian Qu; Xue Li; Carol J Cardona; Zheng Xing (PLoS ONE)
Human infections with avian influenza viruses including H5, H7 and H9 hemagglutinin subtypes occur at a low rate. Among human infections with H7 viruses, regional outbreaks with H7N2, H7N3, H7N7 and H7N9 have been documented. Early in 2018, a human infection with a novel H7N4 avian influenza virus was reported in Jiangsu, China. This study is aimed at understanding the probable origin and molecular features of this emerging H7N4 virus. Genomic segments encoding hemagglutinin (HA) and neuraminidase (NA) of H7Nx and HxN4 viruses were compared with this H7N4 strain by alignment and phylogenetic tree analysis. Phylogenetic analysis indicated that the human H7N4 virus probably originated from multiple reassortments of avian H7N7 and H8N4 viruses for its HA and NA, respectively, and likely a regional uncharacterized virus for its internal segments. Our data excluded that circulating avian H9N2 viruses were the origin of the H7N4 internal segments, unlike the human H5N1 and H7N9 viruses that both had H9N2 backbones. This index case provided a unique opportunity to examine viral mutations by directly comparing the human isolate with its closest viral relatives isolated from avian species from the patient's farm, which may suggest critical mutations required for viral adaptation in humans. Whole-genome scanning was performed and the sequences of the human and related avian H7N4 isolates were compared. Mutations in PB2 (E627K), PB2 (K683T), PB1-F2 (N47S), HA (N283D), HA(K321E), NA(A137V), NA(K296R) and M2 (C19Y) were identified in the human isolate while no mutations were found in PB1, NP, NS1, and NS2 of the human H7N4 compared to the avian H7N4 viruses. Our data in this report provide further evidence for the genesis of this novel H7N4 virus with a multi-reassortment model and show molecular changes that might be responsible for the transmission of this virus from chickens or ducks to and subsequent replication in humans.